Biomethane production from vinasse in upflow anaerobic sludge blanket reactors inoculated with granular sludge - Barros, Valciney Gomes de [UNESP] (2016)
The main objective of this study was to evaluate the anaerobic conversion of vinasse into biomethane with gradual increase in organic loading rate (OLR) in two upflow anaerobic sludge blanket (UASB) reactors, R1 and R2, with volumes of 40.5 and 21.5 L in the mesophilic temperature range. The UASB reactors were operated for 230 days with a hydraulic detection time (HDT) of 2.8 d (R1) and 2.8-1.8 d (R2). The OLR values applied in the reactors were 0.2-7.5 gtotalCOD (L d)-1 in R1 and 0.2-11.5 gtotaiCOD (L d)-1 in R2. The average total chemical oxygen demand (totaiCOD) removal efficiencies ranged from 49% to 82% and the average conversion efficiencies of the removed totaiCOD into methane were 48-58% in R1 and 39-65% in R2. The effluent recirculation was used for an OLR above 6 gtota,COD (L d)(-1) in R1 and 8 g(total)COD (L d)(-1) in R2 and was able to maintain the pH of the influent in R1 and R2 in the range from 6.5 to 6.8. However, this caused a decrease for 53-39% in the conversion efficiency of the removed totaiCOD into methane in R2 because of the increase in the recalcitrant COD in the influent. The largest methane yield values were 0.181 and 0.185 (L) CH4 (g(total) COD removed)-1 in R1 and R2, respectively. These values were attained after 140 days of operation with an OLR of 5.0-7.5 g(total)COD (L d)(-1) and totaiCOD removal efficiencies around 70 and 80%. (C) 2016 Sociedade Brasileira de Microbiologia. Published by Elsevier Editora Ltda. This is an open access article under the CC BY-NC-ND license